2012
DOI: 10.1111/gcb.12087
|View full text |Cite
|
Sign up to set email alerts
|

Land use causes genetic differentiation of life‐history traits in Bromus hordeaceus

Abstract: There is increasing evidence that species can evolve rapidly in response to environmental change. However, although land use is one of the key drivers of current environmental change, studies of its evolutionary consequences are still fairly scarce, in particular studies that examine land-use effects across large numbers of populations, and discriminate between different aspects of land use. Here, we investigated genetic differentiation in relation to land use in the annual grass Bromus hordeaceus. A common ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 70 publications
2
37
1
Order By: Relevance
“…However, this did not lead to local adaptation to climate or soil, sensu Kawecki & Ebert (). Since the genetic differences could not be related to the studied treatment conditions, they might be due to selection for an environmental factor that was not recorded in this experiment, for example, differences in land use (Stöcklin et al ., ; Völler et al ., ) or competition (Kindell et al ., ; Bischoff et al ., ). Alternatively, the observed genetic differences might be due to maternal environmental effects (Roach & Wulff, ), mutations and genetic drift (Silvertown & Charlesworth, ) or founder effects (Linhart & Grant, ).…”
Section: Discussionmentioning
confidence: 98%
“…However, this did not lead to local adaptation to climate or soil, sensu Kawecki & Ebert (). Since the genetic differences could not be related to the studied treatment conditions, they might be due to selection for an environmental factor that was not recorded in this experiment, for example, differences in land use (Stöcklin et al ., ; Völler et al ., ) or competition (Kindell et al ., ; Bischoff et al ., ). Alternatively, the observed genetic differences might be due to maternal environmental effects (Roach & Wulff, ), mutations and genetic drift (Silvertown & Charlesworth, ) or founder effects (Linhart & Grant, ).…”
Section: Discussionmentioning
confidence: 98%
“…The response of vegetation composition to land use depends on the interaction of its components, with some overriding, mitigating, or reinforcing the effects of others, depending on how the specific trait focused on is controlled by the suite of environmental drivers (Socher et al., ; Völler, Auge, Bossdorf, & Prati, ). In our study, frequently mown plots were highly fertilized (Spearman ρ = 0.648, p < .01), whereas intensively grazed plots were, if at all, only rarely mown (Spearman ρ = −0.713, p < .01).…”
Section: Discussionmentioning
confidence: 99%
“…Exploratories and the three studied functional traits. This contrasts with previous studies in 245 the Biodiversity Exploratories (Völler et al, 2013(Völler et al, , 2017 as well as in other systems that 246 demonstrated land use-related phenotypic changes in plants (e.g. Aarssen & Turkington, 247 1985a, b, c, 1987; Lennartsson et al, 1997;Briggs, 2009).…”
Section: No Relationships With Land Use 243mentioning
confidence: 69%
“…As already explained above, 251 our study did not lack statistical power, and it covered a broad range of land use intensities, 252 also compared to previous studies. Moreover, although there is some interannual variation in 253 land use in the Biodiversity Exploratories (Blüthgen et al, 2012;Allan et al, 2014), which 254 could potentially impede the impacts of natural selection, previous studies already found land 255 use-related differentiation of plant phenotypes in our system (Völler et al, 2013(Völler et al, , 2017. It is 256 also known from other studies that that a couple of years can be enough for stable shifts in 257 plant phenotypes between differential management (Briggs, 2009).…”
Section: No Relationships With Land Use 243mentioning
confidence: 84%